2013
DOI: 10.3390/s131216330
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive High-Throughput Single-Cell Analysis of HIV Protease Activity Using Ratiometric Flow Cytometry

Abstract: Abstract:To effectively fight against the human immunodeficiency virus infection/ acquired immunodeficiency syndrome (HIV/AIDS) epidemic, ongoing development of novel HIV protease inhibitors is required. Inexpensive high-throughput screening assays are needed to quickly scan large sets of chemicals for potential inhibitors. We have developed a Förster resonance energy transfer (FRET)-based, HIV protease-sensitive sensor using a combination of a fluorescent protein pair, namely mCerulean and mCitrine. Through e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…HIV-1 proteases is indispensable enzymes in the HIV life cycle and is considered one of the most important targets in anti-HIV drugs development [ 24 , 29 ]. Pepsin and HIV-1 are in the family of aspartic proteases with similar primary structure, the same activating mechanism and are inactivated by pepstatin A inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…HIV-1 proteases is indispensable enzymes in the HIV life cycle and is considered one of the most important targets in anti-HIV drugs development [ 24 , 29 ]. Pepsin and HIV-1 are in the family of aspartic proteases with similar primary structure, the same activating mechanism and are inactivated by pepstatin A inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze HIV protease (PR) activity in single viral particles we chose to employ Förster resonance energy transfer (FRET), a technique previously used to monitor PR activity in cell-free and cell-based assays [18][19][20][21] . We employed the mUKG-mKOκ fluorescent protein pair based on its good spectral separation, compatibility with a wide range of flow cytometry instruments, and high quantum yield that reflects efficient energy transfer between the fluorescent proteins.…”
Section: Generation Of a Fret-based Reporter (Viper) For Analysis Of mentioning
confidence: 99%
“…One potential application of our synthetic device could be as a detection assay for screening the library of drug-resistant HIV-1 protease mutants and inhibitors in mammalian culture cells using different reporters, including cell toxic proteins as the selection markers. The advantages of using cell line–based assays for HIV-1 protease activity have already been reported; authors used different HIV-1 protease precursors (GFP-PR or Gal4-PR) or probe proteins, such as Förster resonance energy transfer-based HIV-1 protease-sensitive sensors. , Through experimental implementation of our signaling device, we have found that it is also faster than two-round phenotyping assays for testing HIV-1 isolates …”
mentioning
confidence: 92%
“…The advantages of using cell line−based assays for HIV-1 protease activity have already been reported; authors used different HIV-1 protease precursors (GFP-PR 18 or Gal4-PR 23 ) or probe proteins, such as Forster resonance energy transfer-based HIV-1 protease-sensitive sensors. 24,25 Through experimental implementation of our signaling device, we have found that it is also faster than two-round phenotyping assays for testing HIV-1 isolates. 26 The primary purpose of the described device is the targeting of essential viral function, regardless of the specific sequence or spatial structure of the particular viral components.…”
mentioning
confidence: 99%